Elevated atmospheric CO2 delays the key timing for split N applications to improve wheat (Triticum aestivum L.) protein composition - Pan, Yue; Han, Xue; Xu, Huasen; Wu, Wei; Liu, Xiaoming; Li, Yingchun; Xue, Cheng (Frontiers in Plant Science, 2023)
Late stage nitrogen (N) applications following basic fertilization are commonly used to ensure grain yield and increase grain protein content in wheat. Split N applications at the late growth stage of wheat are an effective measure to improve N absorption and transport and thus increase grain protein content. However, whether split N applications can alleviate the decrease in grain protein content induced by elevated atmospheric CO2 concentrations (e[CO2]) remains unclear. In the present study, a free-air CO2 enrichment system was used to investigate the effects of split N applications (at booting or anthesis) on grain yield, N utilization, protein content, and the composition of wheat under atmospheric (ACO2; 400 ± 15 ppm) and elevated CO2 concentrations (ECO2; 600 ± 15 ppm). The results showed that wheat grain yield and grain N uptake increased by 5.0% (being grains per ear by 3.0%, 1000-grain weight by 2.0%, and harvest index by 1.6%) and 4.3%, respectively, whereas grain protein content decreased by 2.3% under ECO2 conditions. Although the negative effect of e[CO2] on grain protein content was not alleviated by split N applications, gluten protein content was enhanced due to the alteration of N distribution in different protein fractions (albumins, globulins, gliadins, and glutenins). Compared to that without split N applications, the gluten content of wheat grains increased by 4.2% and 4.5% when late stage N was applied at the booting stage under ACO2 and anthesis under ECO2 conditions, respectively. The results indicate that rational handling of N fertilizers may be a promising approach to coordinating grain yield and quality under the effects of future climate change. However, compared to ACO2 conditions, the key timing for improving grain quality by split N applications should be postponed from the booting stage to anthesis under e[CO2] conditions.